KRITIK TERHADAP WACANA KESETARAAN GENDER AMINA WADUD - Arif Abdul Malik; Achmad Yaman; Sunaryanto (STAI DI AL-HIKMAH, 2024)
This research aims to understand Amina Wadud's concept of gender equality and the relevance of this concept to da'wah. The gender equality discourse has become a major problem in Da'wah. All things in Islam that are against the spirit of equality are challenged. One of the famous figures who challenged it is Amina Wadud Muhsin, an American feminist activist who influenced da'wah by proposing the idea of gender equality in Qur'an. This research is library research by using descriptive qualitative methods. The results of this study show that Amina Wadud's gender equality discourse contradicts the values of Islamic dakwah because the term gender itself contains values that contradict Islam. Therefore, the discourse of gender equality essentially undermines the social life of the Islamic community, which upholds diversity and differences.